2021
DOI: 10.38079/igusabder.845736
|View full text |Cite
|
Sign up to set email alerts
|

Üniversite Öğrencilerinin Cinsel Mitlere Bakış Açısı ve İlişkili Faktörler

Abstract: Bu çalışmada Sağlık Bilimleri Yüksekokulunda okuyan öğrencilerin cinsel mitler ile ilgili düşüncelerini değerlendirmek amaçlanmıştır. Yöntem: Çalışma bir vakıf üniversitesinde öğrenim gören 325 öğrenci ile yüz yüze görüşerek gerçekleştirilmiştir. Araştırmanın verileri "Tanıtıcı Bilgi Formu" ve "Cinsel Mitler Ölçeği" kullanılarak toplanmıştır. Verilerin analizinde tanımlayıcı istatistikler, Mann-Whitney U Testi, Kruskal-Wallis Testi ve Spearman rho korelasyon testi kullanılmıştır. Bulgular: Çalışmaya katılan öğ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In the study, it was found that male students believed in sexual myths at a higher level. In similar studies conducted on university students, it has been reported that male students have more sexual prejudices in comparison to female students (Evcili & Golbasi, 2017; Güdül et al, 2020; Örüklü et al, 2021). Patriarchal societies have a tendency to raise males in a more active and dominant fashion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the study, it was found that male students believed in sexual myths at a higher level. In similar studies conducted on university students, it has been reported that male students have more sexual prejudices in comparison to female students (Evcili & Golbasi, 2017; Güdül et al, 2020; Örüklü et al, 2021). Patriarchal societies have a tendency to raise males in a more active and dominant fashion.…”
Section: Discussionmentioning
confidence: 99%
“…It was found in the study that the students who found their level of knowledge about sexuality and sexual health sufficient believed in sexual myths at a higher level. In similar studies carried out with the participation on university students, knowledge/education about sexuality was shown to reduce believing in sexual myths (Evcili & Golbasi, 2017; Örüklü et al, 2021). As the level of knowledge about sexuality increases, misbeliefs about sexuality and the potential risks it may create decrease (Sarpkaya Güder & Tekbaş, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations